Healthy and Ready to Learn: Effects of a School‐Based Public Health Insurance Outreach Program for Kindergarten‐Aged Children. (10th December 2017) - Jenkins, Jade Marcus
ABSTRACT: BACKGROUND: Rates of child insurance coverage have increased due to expansions in public programs, but many eligible children remain uninsured. Uninsured children are less likely to receive preventative care, which leads to poorer health and achievement in the long term. This study is an evaluation of a school‐based health insurance outreach initiative, "Healthy and Ready to Learn, " aiming to identify and enroll uninsured kindergarteners in areas of high economic need in 16 counties in North Carolina. METHODS: Regression discontinuity design and difference‐in‐differences analyses were used to estimate the effect of the initiative on Medicaid and CHIP enrollment (primary outcome) and preventive care use (well‐child visits; secondary outcome). Focus groups and key‐informant interviews were conducted to assess best practices and identify barriers to outreach for child enrollment. RESULTS: The initiative increased enrollment rates by 12.2% points and increased well‐child exam rates by 8.6% points in the RD models, but not differences‐in‐differences, and did not significantly increase well‐child visits. CONCLUSIONS: Findings demonstrate the potential benefits of using schools as a point of intervention in enrolling young children in public health insurance and as a source of trusted information for low‐income parents.